2003
DOI: 10.1007/bf02481064
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of plastic shrinkage cracking in fiber reinforced concrete using image analysis and a modified Weibull function

Abstract: Numerous strategies have been advocated to reduce the potential for plastic shrinkage cracking in concrete through mixture proportioning, curing methods, or the use of fiber reinforcement. The effectiveness of each approach must be adequately quantified to determine whether the additional initial cost of each strategy is justified. The majority of current research to characterize plastic shrinkage cracking in concrete relies on manual crack observation and measurement that is typically only performed at select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(57 citation statements)
references
References 14 publications
5
47
0
Order By: Relevance
“…This method is very straight forward and is especially attractive considering the matrix nature of the pixel arrangement within an image. However, as stated by Qi et al [24], when the direction of the crack changes, due to such factors as the presence of aggregates or fibres, and becomes nearly horizontal, the crack width, locally, would be greatly overestimated. In fact, as soon as the direction of the crack deviates from the global direction of propagation, the crack width measured perpendicularly to the global or local directions of propagation differs, a difference that rapidly increases as the angle of deviation increases.…”
Section: Crack Widthmentioning
confidence: 93%
See 2 more Smart Citations
“…This method is very straight forward and is especially attractive considering the matrix nature of the pixel arrangement within an image. However, as stated by Qi et al [24], when the direction of the crack changes, due to such factors as the presence of aggregates or fibres, and becomes nearly horizontal, the crack width, locally, would be greatly overestimated. In fact, as soon as the direction of the crack deviates from the global direction of propagation, the crack width measured perpendicularly to the global or local directions of propagation differs, a difference that rapidly increases as the angle of deviation increases.…”
Section: Crack Widthmentioning
confidence: 93%
“…For instance, Qi et al [24] used image analysis to measure the crack width of plastic shrinkage cracks formed along a stress raiser on slab specimens. They adopted an approach in which the crack width was determined to be the length of the segments resulting from subtracting a certain grid mask, consisting of equally spaced lines in the perpendicular direction of the stress raiser, from the binary image of the cracks.…”
Section: Crack Widthmentioning
confidence: 99%
See 1 more Smart Citation
“…Husain and Nijad (2001) have also reported that there is no long-term benefit, in terms of compressive strength, from using curing compounds. The inclusion of polypropylene fibers was also found to eliminate plastic shrinkage cracking in concrete specimens subjected to simulated hot weather (Al-Tayyib et al 1988;Banthia et al 1996;Qi et al 2003). …”
Section: Introductionmentioning
confidence: 98%
“…Another technique uses a small plate to measure free plastic shrinkage, with no embedment (Almusallam et al 1998;Al-Amoudi et al 2006;Bella et al 2009). A specific mold with embedding at the bottom has also been used (Qi et al 2003;Sivakumar & Santhanam 2007). These methods do not simulate stress fields that are produced in reality, as stated by Banthia (Banthia et al1996;, who has developed a method to produce realistic shrinkage conditions.…”
Section: Introductionmentioning
confidence: 99%